Optimizing solar energy for power management system of a moon orbitor - Yow, Lip Pheng. (2012)
Student satellite projects have been increasing throughout the world due to the tremendous educational opportunities it could provide. Today, there are many university student groups who have engaged themselves into building micro and nano satellites for scientific research. In this project, the objective was to develop a prototype step-down DC-DC (Buck) converter for the European Student Moon Orbitor (ESMO) microsatellite. This prototype was built with discrete components and was subsequently enhanced to fulfil the project requirements. Such requirements include an efficiency threshold, a well-regulated output voltage as well as a redundancy setup for contingency. The developed Buck converter utilises the Bootstrap base drive circuitry to ensure optimum performance. The low voltage gate driver is powered by the high voltage mains, supplied through the author's auxiliary supply circuit which was designed to keep the losses to the minimum. Other additional components were also added to improve the output voltage ripple to achieve a switching noise which is less than 5%. A real-time closed loop control was incorporated to the Buck converter by the addition of an embedded controller (MCU). The MCU was programmed with a digital Proportional-Integral (PI) algorithm to achieve a regulated constant output voltage with large variations of input voltage over the range of 50-150V. The MCU is also used to control the Solid-State Relay (SSR) switch in a redundancy circuit, which was built for extra reliability. Last of all, a fundamental idea to manage heat dissipation was also proposed.